BETA DIVERSITY AND COMMUNITY DIFFERENTIATION IN DRY PERENNIAL SAND GRASSLANDS - BARTHA, S.; CAMPETELLA, G.; KERTESZ, M.; HAHN, I.; KROEL-DULAY, GY.; REDEI, T.; KUN, A.; VIRAGH, K.; FEKETE, G.; KOVACS-LANG, E. (Annali di Botanica, 2011)
The spatial variability of species composition was studied in perennial sand grasslands in Hungary at multiple scales. Three sites were compared along an aridity gradient. Existing differences in climate along this ca. 200 km gradient correspond to regional climate changes predicted for the next 20-30 years. Six stands of Festucetum vaginatae grasslands were selected at each site within 400 x 1200 m areas for representing the coarse-scale within-site heterogeneity. Fine-scale compositional heterogeneity of vegetation within stands was sampled by recording the presence of species along 52 m long circular belt transects of 1040 units of 5 cm x 5 cm contiguous microquadrats. This sampling design enabled us to study the patterns of species combinations at a wide range of scales. The highest variability of plant species combinations appeared at very fine scales, between 10 cm and 25 cm. Differences in beta diversity along the gradient were scale-dependent. We found a decreasing trend of beta diversity with increasing aridity at fine scale, and on the contrary, an increasing trend at landscape scale. We conclude that the major trend of the vegetation differentiation due to aridity is the decrease of compositional variability at fine-scale accompanied by a coarse-scale diversification.